The socio-emotional digital literacy (SEL-D) model: confirmatory factor validation of a five-dimension hierarchical structure among adolescents - Yulian Hermanus Wenno; Nono Hery Yoenanto; Rusnawati Ellis; Cynthia Petra Haumahu; Criezta Korlefura (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
The rapid digitalization of adolescents' social environments has intensified the need for competencies that integrate technological skills with socio-emotional awareness and ethical digital behavior. However, existing digital literacy instruments predominantly capture technical and informational dimensions, and no psychometrically validated instrument has yet operationalized the five CASEL competencies as an integrated construct within digital contexts. This study aimed to validate the Socio-Emotional Digital Literacy (SEL-D) model, a hierarchical construct comprising five dimensions: digital self-awareness, digital self-regulation, digital social awareness, digital relationship skills, and responsible digital decision-making. A 30-item instrument, adapted from established SEL and digital literacy measures, was refined through expert content validation involving three experts (item-level Content Validity Index ≥ 0.80). Employing a cross-sectional survey design, data were collected from 139 senior high school students aged 15–18 years, selected through stratified random sampling across grade levels and school types in Ambon, Maluku Province, Indonesia, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model demonstrated satisfactory psychometric properties, with composite reliability ranging from 0.857 to 0.944, Average Variance Extracted from 0.583 to 0.729, and acceptable global model fit (SRMR = 0.098). The higher-order SEL-D construct significantly predicted all five dimensions (β = 0.388–0.928, p < 0.001), most strongly digital relationship skills and social awareness (both β = 0.928; R² = 0.861). As a confirmatory validation of a regionally adapted instrument rather than the development of a new framework, this study provides initial, regionally bounded empirical evidence supporting the multidimensional SEL-D model and underscores the importance of integrating emotional and ethical dimensions into digital literacy education.